Aerial survey method: The experience of Kenya - Taiti, S.W. (International Livestock Centre for Africa, 1981)
Evaluates Kenyan experience of aerial survey from 1968 to 1978, mentioning methods applied, projects & sample design as well as levels of accuracy & innovations introduced.